Qishashun-Nabiyyīn Lil-Athfāl (2017) and Kalam-Qu: Stories in The Qur'an (2018) in Intertextual Relationships - Eva Farhah (CMES (Center of Middle Eastern Studies), 2021)
Research on works that adopt the stories contained in the Al-Qur'an, needs to be examined to find out the originality of the story or the creativity of the authors that are contained in the works. Among the works that adopt the text of the Qur'an are the work entitled Qishashun-Nabiyyīn lil-Athfāl by Abi Al-Hasan Ali al-Hasan an-Nadwiy (2017) and the work Kalam-Qu: The stories in Al- The Qur'an by Jamal Qasim (2018). Both of these works are intended for children. This is the reason these two works are studied. The problem in this study is how the intertextual relationship between the two texts. Intertextual theory is used to study these problems. Thus, the aim of this study is to find and describe the intertextual relationship between the two works. The results of the research show that the transformation text follows the hypogram text. Apart from that, there are also differences between the stories contained in the two works. This happens because the author's or creator's purpose is to show his expertise in making works that are interesting and interesting to the readers.